On the emergence of inflection classes - Ömer DEMİROK (Dilbilim Araştırmaları Dergisi, 2022)
Laz has a rich verb classification system. While the language presents robust morphological correlates of argument structure, it also exhibits finer morphological distinctions that have been argued to encode less canonical semantic features. This paper argues that these distinctions merely constitute inflection classes in the synchronic grammar of Laz but could be a residue of a grammar where these semantic features were active in exponent selection.